Tingkat Kepuasan Pasien terhadap Kualitas Pelayanan Obat di Apotek Rio - Mamay Maulana Sobandi; Akhamad Priyadi; Jajang Japar Sodik (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Patient satisfaction with pharmacy services is a crucial indicator in assessing the quality of healthcare services provided. Patient satisfaction is influenced by the comparison between perceived performance and expectations. If service performance exceeds expectations, patients will be highly satisfied. This study aims to measure the level of patient satisfaction with the quality of drug services at Rio Pharmacy. This descriptive study uses primary data obtained through questionnaires completed by respondents. The results show that all five dimensions of service quality received positive ratings. The Responsiveness dimension has the most significant influence with a score of 56, followed by Reliability, Assurance, and Empathy, each with a score of 52, and Tangible with a score of 47. Overall, patients are satisfied with the quality of drug services at Rio Pharmacy.